2016
DOI: 10.1002/jbm.a.35958
|View full text |Cite
|
Sign up to set email alerts
|

The pathology of the foreign body reaction against biomaterials

Abstract: The healing process after implantation of biomaterials involves the interaction of many contributing factors. Besides their in vivo functionality, biomaterials also require characteristics that allow their integration into the designated tissue without eliciting an overshooting foreign body reaction (FBR). The targeted design of biomaterials with these features, thus, needs understanding of the molecular mechanisms of the FBR. Much effort has been put into research on the interaction of engineered materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
416
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(441 citation statements)
references
References 122 publications
(201 reference statements)
10
416
1
14
Order By: Relevance
“…In this sense, none of the evaluated biomaterials were able to shift the inflammatory pattern of MNGCs toward an anti‐inflammatory type. This observation is plausible because MNGCs are formed in a proinflammatory microenvironment as a result of persistent chronic inflammation . Additionally, biomaterial‐induced MNGCs share morphological and biological properties with the pathological inflammatory giant cells observed in sarcoidosis and tuberculosis that are similarly formed in response to persistent chronic inflammation .…”
Section: Discussionmentioning
confidence: 96%
“…In this sense, none of the evaluated biomaterials were able to shift the inflammatory pattern of MNGCs toward an anti‐inflammatory type. This observation is plausible because MNGCs are formed in a proinflammatory microenvironment as a result of persistent chronic inflammation . Additionally, biomaterial‐induced MNGCs share morphological and biological properties with the pathological inflammatory giant cells observed in sarcoidosis and tuberculosis that are similarly formed in response to persistent chronic inflammation .…”
Section: Discussionmentioning
confidence: 96%
“…Once grafted in vivo, our results showed that SCTLAS were properly integrated in the host abdominal wall tissues with no signs of rejection, infection or other complications, thus suggesting that the bioengineered tissues were highly biocompatible, whereas control SM displayed some signs of inflammatory reaction mainly consisting of macrophage cells. Previous works demonstrated that synthetic SM may exert immediate and chronic inflammatory responses after in vivo implantation, although these responses depend on the properties of each individual mesh . In fact, a recent report suggests that the in vivo use of biomaterials could be associated to a foreign body reaction with several phases and stages that may include a chronic inflammation phase with the presence of abundant macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…That is, following placement all materials – regardless of design or composition – are subject to some degree of protein adsorption, an early neutrophil response, and subsequent invasion of the site of implantation by mononuclear phagocytes. While this represents an oversimplification of a complex process (which has been reviewed at length elsewhere [13]), the view that these events – eventually leading to an inflammatory response at the implant surface – represent a negative occurrence has led to a number of approaches to evade the early host immune response including, tuning of surface topography [48], porosity [914], and chemistry [1518] of the material, as well as the use of non-fouling surfaces and coatings [1921] and decorating surfaces with matricellular proteins to prevent non-self recognition [2224]. While these techniques have undoubtedly shown promise, prevention of long-term interaction of protein or cells with implants has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%